Chetti Melaka of the straits: a conceptual paper of millennial intention to consume Peranakan Indian cuisine / Muhamad Jufri Ismail and Muhammad Safuan Abdul Latip - Ismail, Muhamad Jufri; Abdul Latip, Muhammad Safuan (Universiti Teknologi MARA Cawangan Kedah, 2023)
In Malaysia, the Chetti is a minority ethnic group that the locals hardly recognise. As a result, it may lead to the extinction of the ethnic group. In order to sustain food authenticity over generations, heritage cuisines of each ethnic group in Malaysia must keep their originality as food is generally regarded as a reflection of one's identity and an essential component of cultural riches and heritage. Thus, this conceptual paper focuses on the potential predictors that could influence millennials’ intention to consume Peranakan Indian Cuisine, known as Chetti ethnic due to the lack of literature exploring this ethnicity. It is crucial to understand Millennials' preferences as they make up most of the consumer market and will continue to be significant over the following years. The Chetti ethnicity's uniqueness is valuable to the country as it promotes heritage tourism. It is also an effort to educate the community, which leads to the importance of this study.